Impacts Dashboard for Genetic Innovation - Demont, Matty; Lenaerts, Bert (2022)
The Impacts Dashboard for Genetic Innovation was internally launched within CGIAR Genetic Innovation to assist researchers, managers and investors in visualizing Impact Opportunities and prioritizing Seed Product Market Segments (SPMS). The current version 2.0 features 93 indicators of Impact Opportunities across the five Impact Areas (Nutrition, Health and Food Security; Poverty Reduction, Livelihoods and Jobs; Gender Equality, Youth and Inclusion; Climate Change Adaptation and Mitigation; and Environmental Health and Biodiversity) and a cross-cutting category. It features two filters that enable researchers identifying global Impact Opportunities for prioritization at three levels: (1) globally, (2) based on all CGIAR SPMS (Market Segment Footprint), and (3) based on all active CGIAR SPMS that are currently served by Breeding Pipelines. Prioritization can be conducted at seven aggregate levels: (1) CGIAR Regions, (2) CGIAR Sub-regions, (3) Centers, (4) Crops, (5) Breeding Pipelines, (6) SPMS, and (7) Countries. Impact Opportunities are downscaled from national to SPMS levels using Impact Area-specific scaling methods (e.g., based on targeted area, targeted calories produced, targeted production value, share of agricultural GDP, crop-specific greenhouse gas emissions, and crop-specific global genebank accessions). Users can visualize priorities at the three levels for all seven aggregates in three ways: (1) based on a single indicator through a treemap and (2) a global map, or (3) based on multiple indicators through two area charts, one for breadth indicators and another one for incidence indicators. The Priority Setting Dashboard for Genetic Innovation v2.0 is a prototype that will be integrated into the Global Market Intelligence Platform in 2023, which is one of the core innovations of the CGIAR Initiative on Market Intelligence.